Anatomic injury patterns in combat casualties treated by forward surgical teams. Issue 2 (August 2020) - Suresh, Mithun R.; Valdez-Delgado, Krystal K.; VanFosson, Christopher A.; Trevino, Jennifer D.; Mann-Salinas, Elizabeth A.; Shackelford, Stacy A.; Staudt, Amanda M.
Abstract : BACKGROUND: Role 2 forward surgical teams provide damage-control resuscitation and surgery for life- and limb-threatening injuries. These teams have limited resources and personnel, so understanding the anatomic injury patterns seen by these teams is vital for providing adequate training and preparation prior to deployment. The objective of this study was to describe the spectrum of injuries treated at Role 2 facilities in Afghanistan. METHODS: Using Department of Defense Trauma Registry data, a retrospective, secondary data analysis was conducted. Eligible patients were all battle or non–battle-injured casualties treated by Role 2 forward surgical teams in Afghanistan from October 2005 to June 2018. Abbreviated Injury Scale (AIS) 2005 codes were used to classify each injury and Injury Severity Score (ISS) was calculated for each patient. Patients with multiple trauma were defined as patients with an AIS severity code >2 in at least two ISS body regions. RESULTS: The data set included 10, 383 eligible patients with 45, 225 diagnosis entries (range, 1–27 diagnoses per patient). The largest number of injuries occurred in the lower extremity/pelvis/buttocks (23.9%). Most injuries were categorized as minor (39.4%) or moderate (38.8%) in AIS severity, while the largest number of injuries categorized as severe or worse occurred in the head (13.5%). Among head injuries, 1, 872 injuries were associated with a cerebral concussion or diffuse axonal injury, including 50.6% of those injuries being associated with a loss of consciousness. There were 1, 224 patients with multiple trauma, and the majority had an injury to the extremities/pelvic girdle (58.2%). Additionally, 3.7% of all eligible patients and 10.5% of all patients with multiple trauma did not survive to Role 2 discharge. CONCLUSION: The injury patterns seen in recent conflicts and demonstrated by this study may assist military medical leaders and planners to optimize forward surgical care in future environments, on a larger scale, and utilizing less resources. LEVEL OF EVIDENCE: Epidemiological, Level III.